Sharia Business Contracts from the Perspective of Positive Law: An Analysis of Contract Implementation in Islamic Microfinance Institutions - Maulidiana, Lina; Famulia, Ledy (Universitas Internasional Batam, 2025)
The implementation of contracts (akad) in Sharia business agreements within Islamic Microfinance Institutions (IMFIs) often faces challenges due to discrepancies between Sharia principles and the provisions of national positive law. A lack of customer understanding regarding the contracts being applied, as well as weak Sharia oversight, contributes to undermining the legality and fairness of contract execution. This study aims to provide an in-depth analysis of how akad are implemented in IMFIs within the framework of Sharia business contracts and their relevance to Indonesian positive law. This is a descriptive qualitative study using a socio-juridical approach. Data collection techniques include direct observation at three IMFIs, in-depth interviews with managers and clients, and document analysis of the akad contracts used. The data were analyzed thematically through stages of data reduction, data presentation, and conclusion drawing, linked to legal theory and Sharia principles. The findings reveal that contract implementation remains largely administrative and does not reach a substantive understanding of the content and legal consequences of the agreements. Most clients are unaware of the type of akad used, and the contract documents have not fully referred to DSN-MUI fatwas or national legal regulations. The role of the Sharia Supervisory Board has also not been optimal in ensuring the Sharia compliance and legal validity of the contracts. The study concludes that there is both a normative and practical gap between Sharia business principles and positive law in the practice of akad in IMFIs. Future research is recommended to expand the study area and examine the effectiveness of Sharia legal training for IMFI managers as a means to improve the overall quality of Sharia contracts